2018
DOI: 10.1136/vetreco-2017-000271
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic analysis of the angle in the lateromedial projection of the metacarpophalangeal joint and the distal interphalangeal joint in metacarpophalangeal flexural deformities in calves

Abstract: The bone alignment of the metacarpophalangeal joint (MPJ) of the distal interphalangeal joint (DIPJ) in metacarpophalangeal flexural deformity (MPFD) in calves was evaluated by radiography. This study was designed by retrospective study of radiographs. Lateral to medial radiographs of distal forelimbs were taken from 19 MPFD affected calves (35 forelimbs) and 21 normal calves (42 forelimbs). Based on the radiographs, the lateral angles of MPJ were measured from the metacarpal bone axis and proximal phalanx axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Because male calves gain more weight at birth than female calves, there may be a weight disparity between the fetus and the mother, limiting the fetus’s usual mobility within the uterus and eventually leading to the development of constricted limbs. We observed bilateral flexural deformity in all the calves, similar to the findings of Sato et al [ 19 ] and Baltaci et al [ 9 ], who reported a greater bilateral flexural deformity in bovine calves than unilateral deformity. We have recorded a higher prevalence of fetlock deformity than knee or carpal type.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because male calves gain more weight at birth than female calves, there may be a weight disparity between the fetus and the mother, limiting the fetus’s usual mobility within the uterus and eventually leading to the development of constricted limbs. We observed bilateral flexural deformity in all the calves, similar to the findings of Sato et al [ 19 ] and Baltaci et al [ 9 ], who reported a greater bilateral flexural deformity in bovine calves than unilateral deformity. We have recorded a higher prevalence of fetlock deformity than knee or carpal type.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, two techniques, namely the tendon transection method and tendon elongation method, have been employed to correct the deformity based on the type and severity of knuckling, with a success rate of 92% and 100%, respectively. Rashmi et al [ 22 ]; Sato et al [ 19 ] performed transection technique on the SDFT and DDFT in calves with severe MPFD. They have researched 17 limbs of 10 calves with a success rate of 84%.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum MPJ value of 168.1°, which corresponded to the mildest case of MPFD, was measured in the right forelimb of Calf C; the minimum value of 135.0° was measured in the left forelimb of Calf I and corresponded to the most severe case of MPFD. The maximum and minimum values of DIPJ were 211.8° in the right forelimb of Calf A and 197.1° in the right forelimb of Calf H. According to a previous report [ 12 ], the mean joint angles in the forelimbs of normal calves were as follows: MPJ, 175.9° ± 4.6° (95% confidence interval: 174.5–177.4) and DIPJ, 211.9° ± 4.3° (95% confidence interval: 210.7–213.2). The MPJ values of all 17 limbs in the present study were smaller than that in a normal calf limb.…”
mentioning
confidence: 85%
“…Severe MPFD was classified according to previous reports in which the affected animals were forced to walk on the dorsal aspect of the pastern, fetlock or carpus [ 2 , 16 ]. Radiographs of affected limbs were taken as described in a previous report [ 12 ] and analysed using ImageJ (V.1.48; National Institutes of Health, Bethesda, MD, USA). The lateral angles of the metacarpophalangeal joint (MPJ) and distal interphalangeal joint (DIPJ) were measured using the axis lines of the metacarpal bone and each phalanx ( Fig.…”
mentioning
confidence: 99%
“…Numerous studies regarding limb conformation in adult cattle have been conducted and are used for breeding evaluation [ 9 , 15 , 18 , 20 ]. However, reports regarding limb conformation in calves, including limb deformity, are scarce [ 24 ].…”
mentioning
confidence: 99%